VALUE ADDING AND NATURAL PRODUCTS: HOW MUCH DOES INTELLECTUAL PROPERTY MATTER? - Wynberg, R.; Silveston, J.; Lombard, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Southern African countries are actively engaged in natural product development but, in common with other developing countries, typically export their biodiversity as raw materials with little or no processing, technological input or other value adding. Intellectual property rights (IPR) protection for innovations relating to biodiversity has been accelerated by the Trade Related Intellectual Property Rights (TRIPS) agreement of the World Trade Organisation and there is concern that this will strengthen the market power of northern innovating firms and raise prices in developing countries. At the same time there is recognition that IPRs can assist developing countries in obtaining access to technological capacity, and provide commercial opportunities for encouraging inward investment. Virtually all species under commercial development in southern Africa have patents associated with their processing and/or use, mostly under foreign ownership. We ask: (1) what is the role of IPRs in stimulating industrial activity in the southern African natural products sector; and (2) does the existence of IPRs stimulate or restrict value adding in countries of origin of biological material and traditional knowledge? Three southern African species currently traded in global markets are analysed: Harpagophytum sp. (devil’s claw), Aspalathus linearis (rooibos) and Hoodia spp. We conclude that IPRs seldom restrict value adding, but instead stimulate trade and may provide further commercial opportunities. Low awareness amongst local firms, however, prevents such opportunities from being exploited. Low levels of value adding stem from a complex mix of factors including market access, buyer dominance, a lack of strategic alignment amongst producers, and insufficient technical and financial capacity. Acknowledgements: World Intellectual Property Organisation.